The rational design of gCN/a-WOx/Pt heterostructured nanophotocatalysts for boosting the hydrogen generation from the hydrolysis of ammonia borane under visible light - Aksoy, Merve; Korkut, Sibel Eken; Metin, Onder (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In-situ generation of platinum nanoparticles (Pt NPs) supported on graphitic carbon nitride/amorphous tungsten oxide (gCN/a-WOx) binary heterojunctions under white-light irradiation was performed during the hydrolysis of ammonia borane (HAB). The gCN/a-WOx/Pt(IV) nanocomposites including different amount of W were prepared to study their comparative photocatalysis for the photocatalytic HAB. The yielded gCN/a-WOx/Pt nano-catalysts provided a maximum turnover frequency (TOF) value of 419.2 mol H2 mol Pt-1 min-1, which is higher than that of gCN/Pt nanocatalysts (287.7 mol H2 mol Pt-1 min-1). Many advanced analytical techniques comprising ICP-MS, TEM, HAADF-STEM, XRD, XPS, EDX, and BET were used to determine the elemental composition, morphology, elemental distribution, crystal structure, chemical/oxidation state of the surface elements and the textural properties of the nanocatalysts. The characterization results support the forma-tion of wrinkled paper-like amorphous phase WOx (a-WOx) materials in multiple oxidation states over the gCN nanosheets. The photophysical properties of gCN/a-WOx nano -composites were also analyzed by using UV-Vis DRS, PL, and TRES techniques to clarify the contribution of the heterojunction formation between gCN and a-WOx semiconductors to the photocatalytic activity. Owing to the enhanced visible light absorption, suppressed charge recombination, and promoted charge carrier transfer, gCN/a-WOx/Pt nanocatalysts boosted the hydrogen production from the HAB under white-light irradiation by providing 419.2 mol H2 mol Pt-1 min-1 TOF, which is 4.8 times higher compared to the one obtained in dark. A plausible photocatalytic mechanism for the photocatalytic HAB reaction in the presence of gCN/a-WOx/Pt nanocatalysts was suggested based on the results of performed scavenger experiments. The rate law and the activation parameters for the of gCN/a-WOx/ Pt catalyzed HAB were also reported along with kinetic studies. Additionally, a reusability test was performed to understand the stability of gCN/a-WOx/Pt nanocatalysts in the HAB such that the significance of a-WOx species in the enhancement of photocatalytic activity became more pronounced. This study reports for the first time that gCN/a-WOx hetero-junctions are favorable support materials for the in-situ generation of Pt NPs and pro-moting the photocatalytic activity of Pt NPs in the hydrogen generation from the HAB under white-light illumination.& COPY; 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Graphitic carbon nitride; Amorphous tungsten oxide; Platinum nanoparticles; Heterojunction; Photocatalysts; Hydrogen production; Ammonia borane; TITANIUM-DIOXIDE; DEGRADATION; MECHANISM; CATALYSTS; CLUSTERS; FUEL; Chemistry; Electrochemistry; Energy & Fuels